Development of Electronic Physics Modules with a Scientific Approach Using the Lectora Inspire Application in Static Fluid Materials - Pasha, Atika Sella Wulandari; Suharno, Suharno; Fauzi, Ahmad (Jurnal Materi dan Pembelajaran Fisika, 2024)
This research aims to scientifically develop a Physics-based electronic module approach using the Lectora Inspire application on Static Fluid material, knowing the feasibility of the electronic module being developed. The type of research used is R&D (Research and Development), with development procedures using the ADDIE model. However, the procedures carried out only reached the third stage: analysis, design, and Development. The data used in this research are qualitative and quantitative data obtained from research subjects. The analysis stage is carried out by analyzing the needs of teachers and students in Physics learning activities. The design stage is the design of compiling electronic modules according to the results of the needs analysis. The development stage was validated by two expert lecturers as expert validators, three teacher validators (users), and trials by students consisting of 3 students in one-on-one trials, nine students in small group trials, and 96 students in field trials. Product feasibility is obtained based on validation results from expert validators, teacher validators (users), and student trials. The data collection techniques used were documentation and questionnaires, which were analyzed based on Azwar's opinion. Based on the results of the research and discussion, it can be concluded that the results of expert validation obtained an average score of 110, teacher validation of 108.6 from a maximum score of 116, and the average score of one-on-one trial results was 21.33, the average of small group trials was 22.11, and the average of field trials was 23.05 so that The developed electronic module meets criteria very good. Hence, it is very suitable for use in high school learning.